Systematic Comparison of Epidemic and Non-Epidemic Carbapenem Resistant Klebsiella pneumoniae Strains - Koskinen, Katariina; Penttinen, Reetta; Örmälä-Odegrip, Anni-Maria; Giske, Christian G.; Ketola, Tarmo; Jalasvuori, Matti (Frontiers in Cellular and Infection Microbiology, 2021)
Over the past few decades, extensively drug resistant (XDR) resistant Klebsiella pneumoniae has become a notable burden to healthcare all over the world. Especially carbapenemase-producing strains are problematic due to their capability to withstand even last resort antibiotics. Some sequence types (STs) of K. pneumoniae are significantly more prevalent in hospital settings in comparison to other equally resistant strains. This provokes the question whether or not there are phenotypic characteristics that may render certain K. pneumoniae more suitable for epidemic dispersal between patients, hospitals and different environments. In this study, we selected seven epidemic and non-epidemic carbapenem resistant K. pneumoniae isolates for extensive systematic characterization for phenotypic and genotypic qualities in order to identify potential factors that precede or emerge from epidemic successfulness. Studied characteristics include growth rates and densities in different conditions (media, temperature, pH, resource levels), tolerance to alcohol and drought, inhibition between strains, ability to compensate pH as well as various genomic features. Overall, there are clear differences between isolates, yet, only drought tolerance was found to notably associate with non-epidemic K. pneumoniae strains. We further report a preliminary study on the potential to control K. pneumoniae ST11 with an antimicrobial component produced by a non-epidemic K. pneumoniae. This component initially restricts bacterial growth, but stable resistance develops rapidly in vitro.